Case Report: Dupilumab Successfully Controls Severe Eczema in a Child With Elevated IgE Levels and Recurrent Skin Infections - Joshi, Tejas P.; Anvari, Sara; Gupta, Meera R.; Davis, Carla M.; Hajjar, Joud (Frontiers in Pediatrics, 2021)
The efficacy of dupilumab in pediatric patients with hyper-IgE (HIGE) syndrome is not known. Here we present the case of a child with HIGE syndrome in whom dupilumab treatment led to remarkable control of his eczema and recurrent skin infections. We also review the use of dupilumab in other patients with HIGE syndrome. Our case supports the notion that dupilumab may have a seminal application in treating the severe atopic symptoms that are seen in HIGE syndrome.